Yellow-sticker shopping as competent, creative consumption - Kelsey, Sarah; Morris, Carol; Crewe, Louise (Wiley, 2018)
This paper presents the preliminary findings of an empirical study into a specific and novel form of contemporary consumption: ‘yellow sticker shopping’. This type of consumption involves the active targeting for purchase of food products that have been reduced in price because they are approaching their expiry date. Given the complexities of food provisioning in austerity Britain, that include both non-conventional sites like markets and food banks as well as conventional ‘discounters’ and high street supermarkets the analysis reveals how this form of food provisioning goes far beyond the ‘cost-saving’ accounts that might be expected. The research uses autoethnographic material in the form of vignette, constructed around research conducted in the North of England, together with analysis of an online discussion forum. Data are thematically analysed using literature on shopping and supermarkets and then organised according to the three dimensions of social practice: materials, competences and meanings. The paper makes three key contributions in relation to the practice of yellow sticker shopping. Firstly, that it has distinct spatial and temporal qualities and the role played by the space of the supermarket and its associated fixtures and technologies is important. Secondly, that the uncertain supply of yellow sticker goods results in unpredictability. Successful shopping is celebrated and characterised in ways other than the drudgery often associated with the weekly shop. Thirdly, it reveals an assemblage of competences, skills and knowledge not only in relation to grocery shopping but that take place in the home, around food, its storage and preparation and cooking and recipe knowledge. The paper concludes by outlining further planned research associated with the practice of yellow sticker shopping that will contribute to ongoing study into the alternative modes of food provisioning and their spatialities that are characteristic of life in contemporary Britain.